A case report of eruptive pruritic papular porokeratosis with atopic dermatitis treated with upadacitinib: a novel therapeutic perspective - Hu, Lingyu; Xiao, Yujuan; Zhao, Chenxi; Lou, Fanglu (Frontiers in Medicine, 2025)
Eruptive pruritic papular porokeratosis is a rare subtype of porokeratosis, characterized by the appearance of intensely pruritic erythematous papules. Conventional therapies—including antihistamines, corticosteroids, and retinoids—often yield limited clinical benefit. This case report describes a 73-year-old Chinese man diagnosed with eruptive pruritic papular porokeratosis coexisting with moderate-to-severe atopic dermatitis. The patient developed widespread erythematous papules involving the scalp, trunk, and extremities, accompanied by severe pruritus and exudation secondary to scratching. Despite prior treatment with tofacitinib, acitretin, tripterygium glycosides, and antihistamines (epinastine and olopatadine), the patient exhibited a suboptimal clinical response. Consequently, treatment with upadacitinib, a selective Janus kinase 1 inhibitor, was initiated. Within one week, pruritus markedly improved, and the papules began to flatten. After one month of therapy, pruritus had nearly resolved, and the skin lesions showed progressive regression. The patient continued on a reduced dose of upadacitinib, without evidence of relapse or treatment-related adverse events during follow-up. This case highlights the potential of upadacitinib as an effective and well-tolerated therapeutic option for eruptive pruritic papular porokeratosis with concurrent atopic dermatitis, particularly in refractory cases. Further studies are warranted to evaluate its long-term efficacy and safety.